Spectral fingerprinting to evaluate effects of storage conditions on biomolecular structure of filter-dried saliva samples and recovered DNA - Brogna, Raffaele; Oldenhof, Harriëtte; Sieme, Harald; Wolkers, Willem F. (Scientific reports, 2020)
Saliva has been widely recognized as a non-invasive, painless and easy-to-collect bodily fluid, which contains biomarkers that can be used for diagnosis of both oral and systemic diseases. Under ambient conditions, salivary biomarkers are subject to degradation. Therefore, in order to minimize degradation during transport and storage, saliva specimens need to be stabilized. The aim of this study was to investigate the feasibility of preserving saliva samples by drying to provide a shelf-stable source of DNA. Human saliva was dried on filters under ambient conditions using sucrose as lyoprotective agent. Samples were stored under different conditions, i.e. varying relative humidity (RH) and temperature. In addition to assessment of different cell types in saliva and their DNA contents, Fourier transform infrared spectroscopy (FTIR) was used to evaluate the effects of storage on biomolecular structure characteristics of saliva. FTIR analysis showed that saliva dried without a lyoprotectant exhibits a higher content of extended β-sheet protein secondary structures compared to samples that were dried with sucrose. In order to evaluate differences in characteristic bands arising from the DNA backbone among differently stored samples, principal component analysis (PCA) was performed, allowing a clear discrimination between groups with/without sucrose as well as storage durations and conditions. Our results indicated that saliva dried on filters in the presence of sucrose exhibits higher biomolecular stability during storage.